R&D incentives in vertically related markets - Ahmad Reza Saboori Memar; Georg Götz (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
This paper focuses on incentives to invest in research and development (R&D) in vertically related markets. In a bilateral duopoly setup, we consider how process R&D incentives of the firms in both upstream and downstream market depend on the intensity of simultaneous interbrand and intrabrand competition. Among the results: both interbrand and intrabrand competition have twofold effects on R&D incentives. Existence of a vertically related market with imperfect competition lowers both the incentives to invest in process R&D and the competitive advantage through the R&D investment. We will show how the impact of a firm's R&D investments in either market on consumer surplus as well as on the profits of all firms in both markets depends on exogenous parameters.
Keywords: L13; D43; O30; 330; research and development; vertical relations; bilateral oligopoly; product differentiation; process innovation; interbrand and intrabrand competition